Prevention of Fascial Retraction in the Open Abdomen with a Novel Device - Anita Hees; Frank Willeke (Case Reports in Surgery)
The open abdomen requires intensive and specific treatment efforts. Long hospital admissions, treatment duration, high mortality rates, deferred and delayed wound closures with alloplastic materials or elaborate closure techniques, and the need for subsequent surgical procedures justify and call for implementation of new therapy options. The case presented here demonstrates the use of a new product (Fasciotens Abdomen) to prevent fascial retraction in the open abdomen of an extubated, conscious patient with four-quadrant peritonitis after perforated appendicitis. Controlled, anteriorly directed fascial traction of 50-60 Newtons prevented fascial retraction during open treatment of the abdomen. Once edema was reduced, abdominal closure was completed without difficulty. This new form of therapy was well tolerated by the patient and led to a markedly more rapid abdominal closure without mesh or abdominal wall reconstruction.